Do discrepancies in displayed and perceived love acts account for marital satisfaction? - Mihić, Vladimir (Array, 2012)
When investigating marital satisfaction, researchers often take self-reports for granted. However, although an individual may report showing love to his or her spouse in a particular way, there is no guarantee the partner will notice the behavior, much less recognize it as a display of love. In the current study, we investigated whether husbands and wives see their partner expressing love in the ways partners indicate they show it, and if feelings of marital satisfaction are higher among spouses whose reported displays of love are better recognized as such by their partners. In the study, 302 married couples from Croatia and 456 from Serbia reported on love they experience towards their partner, the ways they show love to their partner, the ways their partner shows love to them, and marital satisfaction. Results suggest moderately high correlations between self and partner perceptions for different ways of showing love. In other words, partners generally recognize when their partners show love through various activities, especially for showing love through physical as well as verbal affection. Interestingly, husbands were better than wives at recognizing their spouses’ reported displays of love. For both husbands and wives, reporting that one’s partner expressed love was tied to higher levels of marital satisfaction